2020
DOI: 10.1038/s41598-020-59424-2
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst hatching site is regularly distributed and does not influence foetal development in mice

Abstract: Hatching out from the zona pellucida (Zp) is a crucial step for blastocyst implantation and development. However, it is still unknown whether the location of the hatching site relative to the inner cell mass (ICM) affects embryo implantation and foetal development. Here, we classified hatching blastocysts into three categories, 0° ≤ θ ≤ 30°, 30° < θ ≤ 60°, and 60° < θ ≤ 90°, in which θ is determined based on the relative position of the hatching site to the arc midpoint of the icM. non-surgical embryo transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
6
2
Order By: Relevance
“…Unhatched 4.0‐dpc blastocysts showed the poorest birth rate (5.1%), indicating the adverse influences of both inherently poor embryo quality and its inability to hatch on birth outcome. A recent study by Liu et al found that blastocyst hatch site did not influence the fetal development in mice 13 . The birth rates of 30.67%‐32.94% in their study, which were observed from non‐surgical ET (NSET) using hatching blastocysts with different TEP sites, were much lower than those in our A‐ and B‐site embryos (Table 2).…”
Section: Discussioncontrasting
confidence: 63%
“…Unhatched 4.0‐dpc blastocysts showed the poorest birth rate (5.1%), indicating the adverse influences of both inherently poor embryo quality and its inability to hatch on birth outcome. A recent study by Liu et al found that blastocyst hatch site did not influence the fetal development in mice 13 . The birth rates of 30.67%‐32.94% in their study, which were observed from non‐surgical ET (NSET) using hatching blastocysts with different TEP sites, were much lower than those in our A‐ and B‐site embryos (Table 2).…”
Section: Discussioncontrasting
confidence: 63%
“…Due to the importance of hatching for successful implantation and pregnancy [28,29], we moved forward to delineate the possible mechanisms behind the improved hatching witnessed following NAM treatment. Previously, supplementation of IVM medium with the SIRT1 activator resveratrol improved the quality and the hatching of blastocysts [3].…”
Section: Discussionmentioning
confidence: 99%
“…At late stages of preimplantation embryo development, blastocysts comprising the two distinct parts, the outer trophectoderm (TE) and the inner cell mass (ICM), tend to hatch out of the zona pellucida. This precisely regulated process, the hatching, is crucial for survival, normal development, and implantation of embryos [ 28 , 29 ]. The critical roles of SIRT1 and AKT signaling in controlling the hatching process were reported [ 3 , 22 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For bovine embryos, nearly equal probability of hatching from the embryonic or abembryonic poles has been demonstrated [51]. However, while the issue of the possible influence of the AH site on the hatching rate, blastocyst implantation, and embryo development remains controversial [43,46,47] and requires further study, the proposed technique enables safe, quick, and reliable ZP drilling at both abembryonic and embryonic poles and thus seems to be very useful for improving the AH effectiveness and overall embryo development. Given recent findings [52], LAH at earlier stages of development might have a detrimental effect on the number of cells in the blastocyst.…”
Section: Discussionmentioning
confidence: 96%
“…Rather, controversial data regarding the most preferential site of embryo hatching in humans and other mammalian species have been obtained so far. While some authors have demonstrated that blastocyst hatching in mice and rats usually begins with the protrusion of TE cells out of the ZP [45,46], others have presented contradicting results, showing that most blastocyst hatching sites are close to the ICM [47]. Likewise, in humans, various authors have reported the formation of natural hatching sites close to the ICM [42,48] as well as opposite to the ICM [49,50].…”
Section: Discussionmentioning
confidence: 99%